Impact of Electronic Word of Mouth, Price Perception, and Product Quality on Purchase Decisions at Richeese Factory in Surabaya - Rezhota Gemirangga; Sugeng Purwanto (Golden Ratio of Mapping Idea and Literature Format, 2026)
These findings suggest that practitioners in the fast-food industry should prioritize price-value perceptions and digital reputation management to strengthen their market position for customers of Richeese Factory in Surabaya. The sampling technique employed was convenience sampling, while data analysis was conducted using the Partial Least Squares (PLS) method with the aid of SmartPLS software. The results indicate that all three variables—E-WOM, price perception, and product quality—have a positive and significant effect on purchasing decisions. Among them, price perception has the most dominant influence, followed by product quality and E-WOM. These findings suggest that consumers tend to prioritize the perceived value for the price they pay, while also considering product quality and online opinions when making purchasing decisions.